A Third Generation Water Bath Based Blackbody Source - Fowler, Joel B. (J Res Natl Inst Stand Technol, 1995)
A third generation water bath based black-body source has been designed and constructed in the Radiometric Physics Division at the National Institute of Standards and Technology, Gaithersburg, MD. The goal of this work was to design a large aperture blackbody source with improved temporal stability and reproducibility compared with earlier designs, as well as improved ease of use. These blackbody sources operate in the 278 K to 353 K range with water temperature combined standard uncertainties of 3.5 mK to 7.8 mK. The calculated emissivity of these sources is 0.9997 with a relative standard uncertainty of 0.0003. With a 50 mm limiting aperture at the cavity; entrance, the emissivity increases to 0.99997.